2017
DOI: 10.3390/jsan6040025
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Decision Analysis Methods in the Mobile Cloud Offloading Paradigm

Abstract: Abstract:Mobile cloud computing (MCC) is becoming a popular mobile technology that aims to augment local resources of mobile devices, such as energy, computing, and storage, by using available cloud services and functionalities. The offloading process is one of the techniques used in MCC to enhance the capabilities of mobile devices by moving mobile data and computation-intensive operations to cloud platforms. Several techniques have been proposed to perform and improve the efficiency and effectiveness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 106 publications
(101 reference statements)
0
18
0
2
Order By: Relevance
“…The MCDA concept [11,12] is a collection of various algorithms that support the selection of the best solution among several alternatives to ensure specific application requirements. Thus, in this subsection, we conduct a review of literature that specifically targets the advantages of applying MCDA algorithms and concepts to edge computing.…”
Section: Mcda In Edge Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCDA concept [11,12] is a collection of various algorithms that support the selection of the best solution among several alternatives to ensure specific application requirements. Thus, in this subsection, we conduct a review of literature that specifically targets the advantages of applying MCDA algorithms and concepts to edge computing.…”
Section: Mcda In Edge Computingmentioning
confidence: 99%
“…Based on Table 1 and our previous study [11] in which we described how the most certain and uncertain MCDA methods enhance the offloading process in mobile cloud computing as well as the selection of cloud services in general, we found that the TOPSIS is the most proposed ranking approach in the literature, since it is one of the famous fundamental multi-criteria decision-making ranking approaches in MCDA. The main features of TOPSIS [56] are chosen as the alternatives that simultaneously have the shortest distance from the ideal solution and the farthest distance from the In this paper, we identify and analyze the criteria that have a direct influence on the selection phase and express clearly the most important characteristics of fog and cloud platforms.…”
Section: Ranking Fog/cloud Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangui et. al [6] and Wu [7] published surveys on multiobjective decision-making to offload computation from mobile devices to the cloud. Although these approaches relate to our work, mobile devices are subject to constraints that do not necessarily apply to IoT gateways.…”
Section: State Of the Artmentioning
confidence: 99%
“…Resource orchestration in cloud system is dissimilar from the customary network systems and the characteristics of the operators, cloud's services, and architecture yields some necessities in resource management which should be sensibly addressed [29,30]. It includes discovery, allocation, and monitoring of physical resources, such as RAM, CPU cores, network bandwidth, and disk space.…”
Section: Related Workmentioning
confidence: 99%